2018
DOI: 10.1177/1753193418761266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decrease in radial inclination of distal radius fractures on distal radioulnar joint stability: a biomechanical study

Abstract: We investigated the relationship between the radial inclination of the distal radius and distal radioulnar joint stability. Six fresh-frozen upper extremities were used. Radial inclination was decreased by 10° and 20° and increased by 10° from the original radial inclination. Distal radioulnar joint stiffness was assessed with an intact radioulnar ligament and after partial and then complete sectioning of the radioulnar ligament. Radial angulation deformities significantly increased distal radioulnar joint sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Radial inclination was one of the parameters to assess the quality of reduction in distal radius fracture. Decrease in radial inclination had been shown to increase stiffness of distal radioulnar joint (DRUJ) in neutral, pronation and supination position in cadaveric study [16]. Increase stiffness of distal radioulnar joint would cause increased risk of DRUJ arthritis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Radial inclination was one of the parameters to assess the quality of reduction in distal radius fracture. Decrease in radial inclination had been shown to increase stiffness of distal radioulnar joint (DRUJ) in neutral, pronation and supination position in cadaveric study [16]. Increase stiffness of distal radioulnar joint would cause increased risk of DRUJ arthritis [17].…”
Section: Discussionmentioning
confidence: 99%
“…27 , 28 Theoretically, in vivo ulnar negativity would not only increase tension on the DOB but also increase tension on the TFCC as described by Bessho et al, generating greater stability. 14…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have investigated various factors and approaches that may negate subsequent DRUJ instability after a DRF. For example, Bessho et al 14 reported that DRFs with a decreased radial angulation have increased stiffness in both the setting of an intact or partially sectioned radial ulnar ligament (RUL). Specifically, they suggested that 10° of radial angulation from the original radial inclination should be achieved intraoperatively to minimize the risk of postoperative DRUJ instability.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-articular fractures of the distal radius (IFDR) are commonly encountered traumas in orthopedics. These fractures are caused by low-energy trauma most often attributed to underlying osteoporosis in elderly individuals, and due to high-energy trauma in young and active individuals (1,2). IFDR occurs as a result of falling on the open hand while the elbow is in extension and the wrist is in dorsiflexion (3).…”
Section: Introductionmentioning
confidence: 99%